Analisis Kepuasan Mahasiswa Terhadap Portal Informasi Akademik Universitas Islam Negeri Sumatera Utara : Tinjauan Literatur - Muhammad Irwan Padli Nasution; Calvin Aditya Harahap (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Academic information portals have an important role in supporting the academic process of students in higher education. This study aims to analyze the level of student satisfaction with the academic information portal of the State Islamic University of North Sumatra (UINSU). This study uses a literature-based approach by referring to previous research in the last five years (2019–2024). The results of the analysis show that reliability, responsiveness, data security, information completeness, and interface design are the main aspects that affect the level of student satisfaction. The recommendations given include improving system stability, developing interactive features, and strengthening user data protection.